1999
DOI: 10.1091/mbc.10.9.2905
|View full text |Cite
|
Sign up to set email alerts
|

Rad18 Is Required for DNA Repair and Checkpoint Responses in Fission Yeast

Abstract: To survive damage to the genome, cells must respond by activating both DNA repair and checkpoint responses. Using genetic screens in the fission yeast Schizosaccharomyces pombe, we recently isolated new genes required for DNA damage checkpoint control. We show here that one of these strains defines a new allele of the previously described rad18 gene, rad18-74. rad18 is an essential gene, even in the absence of extrinsic DNA damage. It encodes a conserved protein related to the structural maintenance of chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
280
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(300 citation statements)
references
References 76 publications
(128 reference statements)
19
280
1
Order By: Relevance
“…The Smc5ϩ6 complex together with two recently described non-SMC subunits, Nse1 and Nse2, has been shown to mitigate the effects of various forms of DNA damage (Lehmann et al, 1995;Verkade et al, 1999;Fujioka et al, 2002;McDonald et al, 2003;Harvey et al, 2004). Consistently, we found that nse3-1 cells are sensitive to gamma irradiation, UV light, the topoisomerase I poison camptothecin, and replication inhibition by hydroxyurea (Figure 3, A and B).…”
Section: Nse3-1 Cells Are Hypersensitive To Genotoxic Stresssupporting
confidence: 86%
See 4 more Smart Citations
“…The Smc5ϩ6 complex together with two recently described non-SMC subunits, Nse1 and Nse2, has been shown to mitigate the effects of various forms of DNA damage (Lehmann et al, 1995;Verkade et al, 1999;Fujioka et al, 2002;McDonald et al, 2003;Harvey et al, 2004). Consistently, we found that nse3-1 cells are sensitive to gamma irradiation, UV light, the topoisomerase I poison camptothecin, and replication inhibition by hydroxyurea (Figure 3, A and B).…”
Section: Nse3-1 Cells Are Hypersensitive To Genotoxic Stresssupporting
confidence: 86%
“…It was necessary to overexpress Rad60 from the potent nmt1 promoter to detect the relatively weak interaction with Smc5 and Smc6 (Boddy et al, 2003). It was previously reported that the BRCT domain containing protein, Brc1, is also required for the viability of smc6-X (rad18-X) cells (Verkade et al, 1999). Consistent with codependent functions of Smc5ϩ6 and the Nse proteins, we found that Brc1 is required for the viability of all nse mutants.…”
supporting
confidence: 89%
See 3 more Smart Citations